1987
DOI: 10.1111/j.1471-4159.1987.tb00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm in Pineal N‐Acetyltransferase Activity: Rapid Phase Reversal and Response to Shorter than 24‐Hour Cycles (IV)

Abstract: N-Acetyltransferase (NAT) is an enzyme whose rhythmic activity in the pineal gland and retina is responsible for circadian rhythms in melatonin. The NAT activity rhythm has circadian properties such as persistence in constant conditions and precise control by light and dark. Experiments are reported in which chicks (Gallus domesticus), raised for 3 weeks in 12 h of light alternating with 12 h of dark (LD12:12), were exposed to 1-3 days of light-dark treatments during which NAT activity was measured in their pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…recently been the subject of intensive investigations [Binkley et al, 1981[Binkley et al, , 1987Binkley, 1983;Robertson and Takahashi, 1988b;Zatz, 1989;Zatz and Mullen, 1988a,b;Zatz et al, 19881. In the present study, a more detailed analysis of the circadian clock regulating melatonin biosynthesis in chick pineal gland has been carried out. Furthermore, in parallel experiments the effects of light and clonidine on the rhythm in vivo of pineal NAT activity was examined.…”
Section: Discussionmentioning
confidence: 99%
“…recently been the subject of intensive investigations [Binkley et al, 1981[Binkley et al, , 1987Binkley, 1983;Robertson and Takahashi, 1988b;Zatz, 1989;Zatz and Mullen, 1988a,b;Zatz et al, 19881. In the present study, a more detailed analysis of the circadian clock regulating melatonin biosynthesis in chick pineal gland has been carried out. Furthermore, in parallel experiments the effects of light and clonidine on the rhythm in vivo of pineal NAT activity was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the gross anatomy of the circadian system, however, the neurochemical mechanisms of information transmission within the circadian system in terms of neuro-hormones, neurotransmitters or neuromodulators have not been sufficiently investigated in them (e.g., Evans, 1980;Brown and Nestler, 1985;Takeda et al, 1985). This is a great setback in the study of the circadian system when one envision a rapid progress in the research after melatonin has been identified as a modulatory agent in the vertebrate circadian system (Deguchi, 1979;Binkley et al, 1987). The recent arrival of HPLC with electrochemical detector (ECD) has, however, opened an avenue for research on the role of neurotransmitter monoamines in the circadian clock mechanism in insects, where their contents in tissue samples must be minute.…”
Section: Introductionmentioning
confidence: 97%